Semiotic Ideologies of Race: Racial Profiling and Retroduction - Lele, Veerendra (Recherches sémiotiques / Semiotic Inquiry)

(untitled) (Association canadienne de sémiotique / Canadian Semiotic Association, 2012)
This paper analyses the semiotic features and errors of logic at work in racial profiling and racial reckoning. Anthropologists have long researched the concept of human “race”, including biological, linguistic, archaeological, and cultural approaches to this topic, and anthropologists now largely agree that “race” is principally a cultural concept, not a biological one. Yet practices of race involve inferences about physical attributes including human phenotype. While much attention has been given to understanding how race operates as a discursive form through which power is exercised, less analysis has been done on the “logic” of racial reckoning, and more generally, on the semiosis of race. What semiotic forms and ideologies are at work in racial practices? How do semiotic ideologies of race reproduce cultural distinctions and hierarchies? In short, how does race work semiotically and what can a semiotic analysis of race reveal? This paper examines a particular social practice – racial profiling – and the roles of iconicity and retroduction in it. I argue that iconicity is central to practices of race and that iconicity contributes to erroneous conditional probabilities and the retroductive reasoning that mistakenly serve to justify racial profiling.